Pengaruh Pengetahuan Tentang Dampak Gadget Pada Kesehatan Terhadap Perilaku Penggunaan Gadget Pada Siswa SDN Kebun Bunga 6 Banjarmasin - Septi Anggraeni (Faletehan Health Journal, 2019)
The progress of the age in the field of technology is growing. The technology that is very popular in this era of globalization is a gadget. The use of gadgets in children is increasing. The Academy of American Pediatricians and the Canadian Pediatricians Association stresses the need for limitations in the use of technology in children, children aged 6-18 years are limited to using only 2 hours per day. Children and adolescents who use technology exceed the recommended time limit have health risks. Lack of understanding about the impact of using gadgets makes children behave using it excessively. The purpose of this study was to determine the effect of knowledge about the impact of gadgets on health on the behavior of gadget use in students of Kebun Bunga 6 Banjarmasin Elementary School. This study is an analytical survey research with a cross sectional approach. The population in this study were all students of class VI SD Negeri Kebun Bunga 6 Banjarmasin. The sample in this study is the total of the population as many as 50 students. The results of a simple Linear Regression analysis show the influence of knowledge about the impact of gadgets on health on the behavior of gadget use in students (p value = 0.002) with a large influence of 18.9%. In this case it is necessary to increase students' knowledge about the impact of gadgets on health, because the higher the knowledge will be followed by a decrease in the behavior of using gadgets.